DETERMINING THE COST-BENEFITS OF ERGONOMIC INTERVENTIONS AND FACTORS THAT LEAD TO THEIR SUCCESS - Hal W. Hendrick (Ação Ergonômica)
Managers usually can justify financially supporting a proposed ergonomics intervention only when it is supported by a sound cost benefit analysis. The factors to consider and sources of information for calculating the costs and benefits of proposed ergonomic pro- jects are described. Based upon his review of numerous ergonomics projects, the com- mon characteristics of successful ergonomics interventions gleaned by the author are described and then illustrated by actual documented cases